Radiation tolerance of ceramics—insights from atomistic simulation of damage accumulation in pyrochlores - Devanathan, R.; Weber, W.; Gale, Julian (The Royal Society of Chemistry, 2010)
We have used molecular dynamics simulations to investigate the effects of radiation damage accumulation in two pyrochlore-structured ceramics, namely Gd2Ti2O7 and Gd2Zr2O7. It is well known from experiment that the titanate is susceptible to radiation-induced amorphization, while the zirconate does not go amorphous under prolonged irradiation. Our simulations show that cation Frenkel pair accumulation eventually leads to amorphization of Gd2Ti2O7, and both anion disorder and cation disorder occur during damage accumulation. Amorphization in Gd2Ti2O7 is accompaniedby a density decrease of about 12.7% and a decrease of about 50% in the elastic modulus. In Gd2Zr2O7, amorphization does not occur, because the residual damage introduced by radiation is not sufficiently energetic to destabilize the crystal structure and drive the material amorphous. Subtle differences in damage accumulation and annealing between the two pyrochlores lead to drastically different radiation response as the damage accumulates.